Enhancing Student Character through Discipline Education Grounded in Islamic Values at State Senior High Schools - Ekwan Gunaidi; Muh. Sholeh (Kopertais Wilayah X Jawa Tengah, 2026)
Character education is a critical component in the development of students' personalities and behaviors within the school environment. One character value that assumes a pivotal role is discipline, as it is intrinsically linked to responsibility, adherence to rules, and the self-control capabilities of students. This study aims to analyze the reinforcement of student character through discipline education grounded in Islamic values at SMA Negeri 1 Pagaralam. The research employs a qualitative approach utilizing a case study design. Data collection was conducted through in-depth interviews, observations, and documentation. Data analysis was performed interactively, encompassing the stages of data reduction, data presentation, and conclusion drawing, utilizing Thomas Lickona's theoretical framework of character education (moral knowing, moral feeling, and moral action) alongside the concept of ta'dib in Islamic education to analyze moral and spiritual value-based discipline. The findings indicate that discipline at SMA Negeri 1 Pagaralam is implemented through an educational approach that prioritizes guidance, dialogue, role modeling, and the cultivation of disciplined behavior, rather than merely enforcing punitive measures. Minor infractions by students are typically addressed through persuasive methods to promote internal awareness of the value of discipline. From the perspective of Islamic education, this approach to discipline aligns with the concept of ta'dib, which emphasizes the development of manners, ethics, and moral responsibility among students. The integration of Islamic values such as trustworthiness, accountability, honesty, and exemplary behavior enhances the effectiveness of discipline as a vehicle for character education. This study affirms that discipline education rooted in Islamic values can serve as an effective and contextually relevant strategy for strengthening student character in public schools.